2015
DOI: 10.1080/15427528.2015.1027979
|View full text |Cite
|
Sign up to set email alerts
|

Consortium of Phosphate-solubilizing Bacteria and Fungi for Promotion of Growth and Yield of Chickpea (Cicer arietinum)

Abstract: The combined inoculation of two or more microbial species, such as phosphate-solubilizing bacteria (PSB) and arbuscular mycorrhizal fungus (AMF) and PSB and nitrogen fixers, has often been reported to exert positive effect on growth and yield of various crops; however, reports on dual inoculation of PSB and free-living phosphate-solubilizing fungi (PSF) are hardly available, which makes this study relevant. P-solubilization efficiency (SE) was highest for Bacillus sp.; SE values for RM-2 were highest on the 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 32 publications
1
16
1
2
Order By: Relevance
“…In the present study, RNPK together with PSB resulted in maximum shoot length and fresh and dry biomass of shoot. This increase might be due to releases of higher chlorophyll activities ( Supplementary Figures S1-S3) and more photosynthate availability that increased the growth of the plants [47]. These findings are also in agreement with Saxena, et al [48], who reported that longer root length could be improved by PSB with the chemical fertilizer.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, RNPK together with PSB resulted in maximum shoot length and fresh and dry biomass of shoot. This increase might be due to releases of higher chlorophyll activities ( Supplementary Figures S1-S3) and more photosynthate availability that increased the growth of the plants [47]. These findings are also in agreement with Saxena, et al [48], who reported that longer root length could be improved by PSB with the chemical fertilizer.…”
Section: Discussionsupporting
confidence: 90%
“…AMF and PSF have a synergistic effect on the dissolution and absorption of P 10 , 11 , 24 . PSF increases the soil P pool that can be used by AMF extraradical hyphae to deliver P to plants 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Gupta and Gangwar (2012) in chickpea reported highest chlorophyll content (6.20mg/g fresh leaves) was observed with 1.0 kg AM/ha as soil application + Rhizobium + PSB +RDF. Abbas et al, (2013) Saxena et al, (2015) also recorded high chlorophyll content in maize on co inoculation with TCP over control. The increase in dry matter yield could be due to PGPR effect of inoculated microbe leading to high uptake of nutrients, increased photosynthesis, and increased growth of root and shoot organs, siderophore and phytohormone production, as well as to their capacity to colonize the root system and interact positively with the plant (Viruel et al, 2011).…”
Section: Plant Growth Promoting Activity Of Bacterial Strainsmentioning
confidence: 92%